LITERASI DIGITAL PADA ONLINE TRAINING MARKETING DALAM E-COMMERCE UNTUK MENINGKATKAN PEMASARAN UMKM - Annisa Ekayanti; Nurlaila Maysaroh Chairunnisa; Yuha Nadhirah (Universitas Islam 45 Bekasi, 2022)
The Covid 19 pandemic that occurred in Indonesia, especially in the Sukaraya Indah Housing, Karang Bahagia District, Sukaraya Village, Kab. Bekasi is changing people's lives both in terms of health and economy. In this case, the behavior of MSMEs has an impact, namely in the form of a lack of knowledge about digital marketing using e-commerce. This program was created in this activity in accordance with the problems that exist in MSMEs, namely providing education about digital marketing, training using the Shopee and Tokopedia applications. This activity was carried out on February 17, 2022 at Sukaraya Indah Housing Rt 002 Karang Bahagia Subdistrict, Sukaraya Village, Kab. Bekasi. The method used is in the form of WhatsApp Group and Google Meeting. The impact obtained by the training participants is helping MSMEs to have more insight to change their selling strategy and helping people who want to maintain their business during this fairly difficult pandemic.